A numerical algorithm to find optimum parameters of a flexible-link manipulator arm for performing payload launching. Issue 5 (30th November 2021) - Alipour, Khalil; Tarvirdizadeh, Bahram
Abstract : Purpose: The aim of the current study is proposing a novel framework to attain the optimum value of a flexible arm manipulator parameters for payload launching missions. Design/methodology/approach: The proposed scheme is based on optimal control approach and combines direct and indirect search methods while considering the actuator capacity. Findings: Three nonlinear parameter-optimization problems will be solved to illustrate how the proposed algorithm can be exploited. Employing variational based nonlinear optimal control within the suggested framework, the answer of these problems is highly intertwined to the solution of a set of differential equations with split boundary values. To solve the obtained boundary value problem (BVP), the related solver of MATLAB® software, bvp6c, will be employed. The achieved simulation results support the worth of the developed procedure. Originality/value: For the first time, the optimal parameters of a flexible link robot for object launching are found in the current research. In addition, the actuator saturation limits are considered which enhances the applicability of the suggested method in the real world applications.